Horizontal mergers and uncertainty - Nicolas Le Pape; Kai Zhao (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
This paper analyses the profitability of horizontal mergers in a Stackelberg model and their impact on welfare when there is uncertainty about the marginal costs of the newly merged firms. The authors consider that the merging firms decide their production strategy knowing the actual value of the production cost, while outsiders are a priori uncertain about the exact amount of cost efficiency/inefficiency that will result from the merger. Nevertheless, the key element of the model is that the merged entity can signal its own cost to some rivals (outsider-followers) when it behaves as a leader; while all outsiders remain uninformed when it behaves as a follower. They show that when there is role redistribution, the merging firms always have incentives to merge, irrespective of cost uncertainty, while a merger without role redistribution is ex ante profitable if and only if uncertainty is sufficiently great. As regards the social desirability of mergers, it is found that a merger between leaders always enhances welfare if participants have incentives to merge, such that private and collective interests coincide. Nevertheless, a merger with role redistribution leads to conflict between private and collective interests.
Keywords: D21; D80; L20; L40; 330; Merger; competition authorities; uncertainty; asymmetric information